2020
DOI: 10.3390/app10238704
|View full text |Cite
|
Sign up to set email alerts
|

Leaching Characteristics of Wood Biomass Fly Ash Cement Composites

Abstract: Wood biomass ash (WBA) represents an environmental and economic problem for energy producers, and there have been extensive studies of using WBA as a raw material in construction products. This study investigates the leaching characteristics of WBA cement composites based on testing results. Currently, 70% of WBA is landfilled, and the rest is primarily used in agriculture; therefore, this study also addresses the leaching as a component of environmental safety of these two primary WBA management approaches. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…The chemical composition of the WBAs and cement used in the concrete mixes were compared with the criteria for coal fly ash according to the standard EN 450-1:2013 [ 55 ], Table 5 . According to the results of chemical analysis, the properties of WBA differ significantly from those of coal fly ash, a traditionally known and widely used mineral admixture [ 37 ]. It is also important to emphasize that the chemical composition of WBA can vary significantly depending on the raw material and combustion technology [ 26 , 56 , 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical composition of the WBAs and cement used in the concrete mixes were compared with the criteria for coal fly ash according to the standard EN 450-1:2013 [ 55 ], Table 5 . According to the results of chemical analysis, the properties of WBA differ significantly from those of coal fly ash, a traditionally known and widely used mineral admixture [ 37 ]. It is also important to emphasize that the chemical composition of WBA can vary significantly depending on the raw material and combustion technology [ 26 , 56 , 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, when waste ash is landfilled in non-designated sites, there is also the problem of groundwater pollution due to leaching of heavy metals from WBA or rainwater infiltration, all of which have a negative impact on the ecological system [ 36 ]. Therefore, by binding the heavy metals from WBA in the cement matrix, the use of WBA in low-carbon concrete contributes to the production of an environmentally friendly and cost-effective alternative cementitious material [ 37 ]. To verify an optimum share of WBA as a cement substitute, which has exhibited promising pozzolanic properties, a compromise between the amount of WBA and the downgrade of concrete properties is needed [ 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors [25,41,64] found that the concentration of heavy metals such as Zn, Cd, Pb, and Hg is higher in fly WBA samples than in bottom samples. Therefore, the leaching/stabilization behavior of cementitious composites prepared with fly WBA Values of cumulative leaching in mg/m 2 for different metals (M-Fi-mortar mix with 15% of fly WBA) [65].…”
Section: Ecological Feasibility Of Using Wba As Supplementary Cementi...mentioning
confidence: 99%
“…Utilization of Wood Biomass Ash in Concrete Industry DOI: http://dx.doi.org/10.5772/intechopen.102549 should be analyzed. According to the leaching results obtained by the author [65] for the observed heavy metals (Zn, Cd, CR, Cu, Ni, Pb) on monolithic specimens using 3 types of fly WBA (Figure 6), it was concluded that the leaching of heavy metals was acceptable, i.e., less than the limits according to the Dutch guidelines of the Soil Quality Ordinance [66] (limits for finished building materials according to the Soil Quality Ordinance for Cd: 3.8 mg/m 2 ; Cr: 120 mg/m 2 ; Cu: 98 mg/m 2 ; Ni: 81 mg/m 2 ; Pb: 400 mg/m 2 ; Zn: 800 mg/m 2 ). The same was confirmed by the authors [55,67] when using ash from the combustion of pure wood biomass.…”
Section: Ecological Feasibility Of Using Wba As Supplementary Cementi...mentioning
confidence: 99%
See 1 more Smart Citation